The state of the main arteries, vascular age in patients with arterial hypertension and obesity: the role of leptin and adiponectin - M. E. Statsenko; M. V. Derevyanchenko (Российский кардиологический журнал)
Aim. To study the state of the main arteries and vascular age in conjunction with the level of leptin and adiponectin in patients with arterial hypertension (AH) and obesity.Material and methods. One hundred and twenty patients with AH stage II aged from 45 to 65 years were divided into 3 groups depending on body mass index (BMI). Group 1 was represented by patients with AH and normal BMI, the 2 group was represented by patients with AH and excessive BMI, the 3 group was represented by patients with AH in combination with obesity. A standard clinical examination was performed, the stiffness of the vascular wall was measured by measuring the pulse wave velocity (PWV) of the muscle and elastic vessels (PWVe), vascular age was calculated, and the laboratory markers of obesity were determined.Results. High percentage of visceral obesity was observed: 20,0% among people with normal BMI, 64,4% among overweight people and 100% among people with obesity (differences between 1 and 2, 1 and 3, 2 and 3 groups are reliable). A statistically significant increase in PWVe was detected in patients with AH and obesity in comparison with patients with AH and normal body weight (9,8 [8,5; 11,3] vs 8,0 [79; 8,1] m/s). Vascular age was higher in patients with AH and overweight or obesity compared with patients with AH and normal weight (670 [60,0; 76,0], 68,0 [60,0; 72,0] vs 58,0 [57,0; 60,0] years, respectively). A statistically significant increase in the concentration of leptin (6,9 [4,5; 15,1] vs 19,0 [74; 42,7] vs 53,8 [38,4; 75,8] ng/ml) was detected, as well as a decrease in adiponectin concentration from the 1 to the 3 group (44,9 [36,6; 55,8] vs 16,5 [12,5; 24,7] vs 18,6 [15,3; 22,4] ng/ml, respectively).Correlation analysis revealed the presence of highly reliable relationships between the parameters of rigidity of the main arteries and laboratory markers of obesity.Conclusion. The results indicated a negative effect of hyperleptinemia and hypoadiponectinemia on the elasticity of the vascular wall of the main arteries and the vascular age in hypertensive patients with its combination with overweight or obesity.